2020
DOI: 10.1111/aeq.12362
|View full text |Cite
|
Sign up to set email alerts
|

“So, Is Gentrification Good or Bad?”: One Teacher’s Implementation of the Fourth Goal in Her TWBE Classroom

Abstract: Two‐way bilingual education (TWBE) is guided by three traditional goals: academic achievement, bilingualism/biliteracy, and sociocultural competence. The rapid growth, whitening, and gentrification of TWBE programs have prompted a call for an extension of the three traditional goals to include a fourth one: critical consciousness. This critical ethnography examines how the author and a fifth‐grade TWBE teacher prioritized this fourth goal in the curriculum by positioning gentrification processes impacting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…In conceptual articles, bilingual-education scholars have highlighted the need to include critical consciousness in order to challenge hegemonic ideologies and practices (e.g., Alfaro, 2019;Palmer et al, 2019). In a recent study, Heiman (2021) found an elementary-level teacher's pedagogies prioritizing critical consciousness impacted other teaching facets and lead to generative practices. Freire and Valdez (2017) found that a lack of time, materials, knowledge, and inclination were major obstacles elementary-DL teachers face when implementing culturally relevant pedagogy, especially regarding critical consciousness.…”
Section: Critical-racial Consciousnessmentioning
confidence: 99%
“…In conceptual articles, bilingual-education scholars have highlighted the need to include critical consciousness in order to challenge hegemonic ideologies and practices (e.g., Alfaro, 2019;Palmer et al, 2019). In a recent study, Heiman (2021) found an elementary-level teacher's pedagogies prioritizing critical consciousness impacted other teaching facets and lead to generative practices. Freire and Valdez (2017) found that a lack of time, materials, knowledge, and inclination were major obstacles elementary-DL teachers face when implementing culturally relevant pedagogy, especially regarding critical consciousness.…”
Section: Critical-racial Consciousnessmentioning
confidence: 99%
“…The complexities and myriad demands placed on bilingual and DLBE teachers (Caldas, 2019b;Heiman & Urrieta, 2020;Palmer & Martínez, 2013) at a critical juncture when bilingual education is mired in whitening processes (Chávez-Moreno, 2019;Flores & García, 2017) and gentrification (Chaparro, 2020;Heiman, 2020;Valdez et al, 2016) reveal the urgency to hacer más in the preparation of FMBs (Alfaro & Bartolomé, 2017;Caldas, 2017;Haas & Gort, 2009). We argue that those tasked with preparing FMBs are also key stakeholders in bilingual education and that hacer más in this preparation requires an explicit focus on the fourth goal of DLBE: the development of critical consciousness (Freire, 2020;Alfaro, 2019;Palmer et al, 2019;Rodríguez-Mojica & Briceño, 2019).…”
Section: The Urgency Of Haciendo Más In the Preparation Of Fmbsmentioning
confidence: 99%
“…Their call for more critically conscious relationships between Spanish and bilingual education departments is essential, along with their insistence that this partnership provide rich, culturally relevant opportunities for FMBs to engage with academic Spanish. Their principle focus on academic Spanish is limiting, however, in the current sociopolitical moment characterized by gentrification in bilingual education (Chaparro, 2020;Heiman, 2020;Valdez et al, 2016). We envision an espacio emergente that prioritizes the development of critical consciousness for all stakeholders involved in the preparation of FMBs alongside the improvement of academic Spanish (Alfaro, 2019;Caldas, 2018;Cervantes-Soon, 2018;Heiman & Urrieta, 2019;Rodríguez-Mojica & Briceño, 2019).…”
Section: Conceptualizing An Espacio Emergente In the Preparation Of Fmbsmentioning
confidence: 99%
See 2 more Smart Citations